From Insecurity to Confidence: Exploring Moral Values in “Tall Girl” Movie by Nzingha Stewart - Dian Agatha, Shahnaz; Deni Ariyaningsih, Nyoman (Jurnal Multidisiplin Indonesia, 2024)
This study examines the moral values presented in the "Tall Girl" film directed by Nzingha Stewart. Utilizing a descriptive-qualitative approach, the research identifies and analyzes the moral messages conveyed through the film's narrative and characters. The primary moral values identified include honesty, courage, self-reliance and potential, loyalty and dependability, and love. The analysis reveals that the movie emphasizes themes of self-acceptance, confidence, and overcoming insecurity, particularly relevant to teenagers transitioning to adulthood. By exploring these moral values, the film encourages viewers to embrace their uniqueness, build healthy relationships, and reject societal standards of perfection. The findings highlight the movie's role in promoting positive attitudes and emotional intelligence, demonstrating its potential to impart significant moral lessons to its audience.